Reduction of Erosion Wear of Mean Pressure Cylinder of Steam Turbines Operating Beyond Critical Parameters - V. P. Kascheev; V. A. Khaimov; E. O. Voronov; O. V. Kascheeva; V. N. Sorokin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers problems leading to erosion wear of flowing part of a mean pressure turbine cylinder operating beyond critical parameters. Explanation of erosion wear of flowing part of a mean pressure turbine cylinder which is proved in practice and recommendations for wear reduction are given in the paper